The Concepts and Types of Plant Growth Hormones and Their Role in Field Crop Production - Tekle, Addis Tadesse (International Journal For Research In Agricultural And Food Science, 2019)
This paper is intended to revise those findings in the area of plant growth hormones; concepts, type and their role in field crop production for the better understanding of previous and current research findings. The plant hormones are defined as organic compounds which regulate plant physiological process regardless of whether these compounds are naturally occurring and/or synthetic; stimulating and/or inhibitory; local activators or substances which act at a distance from the place where they are formed. Hormones are chemical signals that are produced in one part of the body /tissue and transported to other parts of the plant bind to a specific receptor and trigger responses in the target cell and tissue. Plant development was thought to be regulated by only five types of hormones; auxins, gibberellins, cytokinins, abscisic acid, and ethylene. However, there is no compelling evidence that has a wide range of morphological effects on plant development. Current study indicate that plant growth hormones has play a significant role in the growth, physiological, biochemical, quality and yield characteristics of pulse crops which include length, fresh and dry weight of root, leaf number, leaf area, leaf area index (LAI), net assimilation rate (NAR), chlorophyll content, photosynthesis, nitrate reductase activity (NR), carbonic anhydrase activity (CA), nutrient accumulation, nitrogen, phosphorus and potassium contents, protein and carbohydrate content and various other growth, yield and quality parameters.. So the present review indicates that the process of growth and development, in addition to the yield and quality of plants is highly affected by the plant growth hormones and plant growth regulators. Finally, the objective of this term paper is to point out those research results in the area of plant growth hormones; their major classifications and role in field crop production through the review of different papers in this area.